Precariousness and its Lexical-Semantic Constellation - Azaovagh de la Rosa, Anisa (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The aim of this article is to frame the category of precariousness in a broad context constituted by a group of authors such as J. Butler, G. Vattimo, J. Habermas or M. Nussbaum. All of them converge, from different interests, in rejecting what Vattimo calls «strong thinking», which provides theoretical solidity and security, but tends toward justify violence. In front of this rejection, and from its theoretical vulnerability or fragility, they opt for «weak thinking» wich is more open to nonviolent ethical politics and interaction.
Keywords: precariousness; violence; weakness; fragility; ethics